Acute Hepatitis and Pancytopenia in Healthy Infant with Adenovirus - Amr Matoq; Asma Salahuddin (Case Reports in Pediatrics)
Adenoviruses are a common cause of respiratory infection, pharyngitis, and conjunctivitis in infants and young children. They are known to cause hepatitis and liver failure in immunocompromised patients; they are a rare cause of hepatitis in immunocompetent patients and have been known to cause fulminant hepatic failure. We present a 23-month-old immunocompetent infant who presented with acute noncholestatic hepatitis, hypoalbuminemia, generalized anasarca, and pancytopenia secondary to adenovirus infection.